PENGARUH MOTIVASI KERJA DAN LEARNING ORGANIZATION TERHADKINERJA GURU YANG DIMEDIASI OLEH KOMITMEN ORGANISASIONA (Studi Pada Guru Smp Negeri Se Kecamatan Batang – Kabupaten Batang) - Santoso, Moehamad; Suhari, Yohanes (Jurnal Ilmiah Telaah Manajemen, 2015)
This study aims to analyze the influence of work motivation, learning organization and organizational commitment to the performance of teachers and the role of organizational commitment mediate the influence of work motivation and learning organization on teacher performance in secondary school teachers in Batang sub-district of Batang district. The population in this study is the teachers of SMP Negeri in Batang sub-district amounted to 256 people. Because the population is relatively large then the sampling with purposive sampling method, that is sampling with certain criteria. In this case researchers used a sample of teachers who have received certification allowance amounting to 188 people. Then from 188 people, who returned the questionnaire answers amounted to 141 people. Data analysis using multiple regression analysis. The result of hypothesis test showed that (1) work motivation has positive effect to organizational commitment, (2) learning organization has positive effect to organizational commitment, (3) work motivation has no effect on teacher performance, (4) learning organization has positive effect on teacher performance, (5) organizational commitment has a positive effect on teacher performance, (6) organizational commitment mediates the effect of work motivation on teacher performance, (7) the direct effect of organizational commitment on teacher performance is greater than indirect influence through organizational commitment. Keywords: Work Motivation, Learning Organization, Organizational Commitment, Teacher Performance